Poziom nakładów materialnych a wyniki ekonomiczne gospodarstw indywidualnych - Wasilewski, Mirosław (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2004)
In the paper the analysis of the relationship between economic results and the level of the material outlays' concentration in private farms is presented. In general, farms with the highest level of the material outlays' concentration were characterized by the highest profitability of land, while in the group of the lowest level of those outlays the profitability was the lowest. In the case of the productivity of land relationships were similar to the case of its profitability. Social and economic efficiency of labour was higher in the group of farms with the highest level of material outlays, what shows that resources and labour outlays were used effectively. In general farms with an average level of material outlays were characterized by the highest profitability of sale, while farms with the highest outlays were characterized by the lowest profitability. It may show that the effectiveness of material outlays decrease with the growth by unit of the level of outlays. One of possible reasons for that tendency, in comparison with the highest profitability of land in the third group of farms, is using purchased materials for the broader scale, what makes farms independent on their resources of land.